PROBLEMATIKA KETERAMPILAN MENYIMAK DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS III SEKOLAH DASAR - Haryanto, Nathania Janani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Listening skills are an essential aspect of language learning, especially in Indonesian language instruction at the elementary school level. However, these skills are often overlooked and perceived as passive by students. This study aims to identify the challenges students face in listening and formulate strategies to improve them. The research uses a qualitative descriptive method with literature review and case studies involving three third-grade elementary school students. The findings indicate various listening barriers, both internal—such as lack of interest and concentration—and external, including monotonous teaching methods and limited learning media. A significant observation involved a student with special needs who showed minimal verbal response, making it difficult to assess listening comprehension. Recommended strategies to enhance listening skills include the use of audio-visual media such as educational cartoons, interactive language games, and storytelling accompanied by instrumental music. These methods have been proven to increase student interest, focus, and comprehension in listening activities.